The battle for Skandia - Flanagan, John (John Anthony) (New York : Philomel Books, 2008)
After Ranger's apprentice Will battles Temujai warriors to rescue Evanlyn, Will's kingdom of Skandia joins forces with rival kingdom Araluen to defeat a common enemy.
Originally published in Australia by Random House Australia Children's Books, 2006, under title Oakleaf bearers.
Keywords: Heroes -- Juvenile fiction; War stories; Heroes -- Fiction; War -- Fiction; Fantasy